2019
DOI: 10.1016/j.ygeno.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of resistin and its plasma levels: Association with obesity and dyslipidemia related to type 2 diabetes susceptibility

Abstract: Resistin, an adipokine, is involved in obesity and Type 2 Diabetes (T2D). The current study evaluates the association between RETN polymorphisms (-638 G/A, -420C/G & -358 G/A) and the risk towards T2D. Controls and T2D patients were enrolled from Gujarat, India. Polymorphisms of RETN were genotyped by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism. For the genotype-phenotype correlation analysis Fasting Blood Glucose (FBG), Body Mass Index (BMI) and plasma lipid profile were used. Plasma le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…SNPs are found in the RETN promoter and 3'-untranslated regions [14]. Genetic variation at the RETN locus carries a risk of several diseases, including the metabolic syndrome and colon cancer [15,16] and those with a functional RETN gene polymorphism at -420 (rs1862513) are at risk of developing type 2 diabetes [17,18], and associated with obesity in Tunisian population [19]. RETN SNPs have been found to correlated with worsening disease in Chinese Han patients with lung cancer [20].…”
Section: Ivyspringmentioning
confidence: 99%
“…SNPs are found in the RETN promoter and 3'-untranslated regions [14]. Genetic variation at the RETN locus carries a risk of several diseases, including the metabolic syndrome and colon cancer [15,16] and those with a functional RETN gene polymorphism at -420 (rs1862513) are at risk of developing type 2 diabetes [17,18], and associated with obesity in Tunisian population [19]. RETN SNPs have been found to correlated with worsening disease in Chinese Han patients with lung cancer [20].…”
Section: Ivyspringmentioning
confidence: 99%
“…These findings also suggest the association of +276G/T (rs1501299) with Non-Alcoholic Fatty Liver Disease (NAFLD), co-morbidity associated with T2D as supported by Wang et al 43 . Additionally, we have also found increased levels of TNFα, Free Fatty Acids (FFA) and resistin in obese patients 17,44 . Since TNFα is shown to be an important regulator of adiponectin multimerization 45 , our observations of increased TNFα, reduced adiponectin transcript and HMW adiponectin levels in obese patients are self-explanatory.…”
Section: Discussionmentioning
confidence: 71%
“…This research demonstrated that TLR4 serves as a receptor mediating the proinflammatory effects of resistin in human cells [153]. RETN 2KB upstream variant rs1862513 C has been found to correlate with a higher BMI [132,133]. This finding is in contrast to a study indicating that Retn KO mice do not manifest any alteration in adiposity [201].…”
Section: Other Cytokinesmentioning
confidence: 97%